Programa de educación ambiental a los niños de la Escuela Héroes del Cenepa del barrio Chinapintza del cantón Paquisha. - Toledo Espejo, Ana Belén (2014)
This work addresses the degree to environmental education for children from the "Heroes Cenepa" School district Chinapintza Region Paquisha province of Zamora Chinchipe; which is a response to the environmental problem experienced by the residents of this mining area. As a result of that activity, developed about 30 years ago, there are environmental conflicts that affect the deterioration of natural resources and the quality of life for residents. The environmental education program focused on the care and protection of water sources Chinapintza neighborhood, arises due to the pressures on this resource for small-scale and artisanal mining activity, and lack of awareness of the population about their watch out. The program comprises theoretical, practical and research elements, and the application of participatory methodologies and leisure, so that students acquire knowledge and develop environmental awareness and attitudes demonstrated through active participation in projects, clubs and programs for the care of the resource water.